국가재난관리체제 관점의 화학사고 대응체계 개선방안에 관한 연구 - 이재석(Lee, Jae-Seok); 최돈묵(Choi, Don-Mook) (한국화재소방학회 논문지, 2015)
Since the hydrofluoric acid spill accident in Gumi in 2012, the current situation has continued to suffer from makeshift responses or feeble national system maintenance in preparing real countermeasures against chemical accidents, regardless of their repeated occurrence and seriousness. Industrial chemical accidents have an enormous ripple effect on the whole country and society. The purpose of this study is to propose ways of establishing directions for the national disaster management system against repeated occurrence of chemical accidents. To achieve this goal, the present study proposed improvement measures of response system for industrial chemical accident through the analysis of the current response system and structural causes of disaster control failure for chemical accidents. 2012년 구미 불산 누출사고 이후 화학사고의 심각성이 대두되고 있으나, 계속적으로 화학사고가 발생함에도 불구하고 임시방편적 대응 혹은 화학 사고에 대한 실질적 대응방안 마련을 위한 국가적 시스템 정비는 미비한 실정이다. 이제 일련의 화학사고가 단순히 기업이나 공장의 화학물질 사고를 넘어 전(全) 국가 및 사회 전반에 엄청난 파급효과를 일으키고 있다. 본 연구는 계속적으로 발생하고 있는 화학 사고에 있어 국가재난관리체계 확립방향의 길을 조금이나마 제시하기 위한 목적으로 연구되었으며, 이러한 연구의 목적을 도달하기 위해 현재 재난관리체계의 문제점, 화학 사고에 대한 재난관리 실패의 구조적 원인 및 사고 대응의 문제점 도출을 통해 화학사고 대응체계에 대한 개선방안을 제시하였다.